2007
DOI: 10.1111/j.1750-3841.2007.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Roselle (Hibiscus sabdariffa) Seed Oil Is a Rich Source of γ‐Tocopherol

Abstract: The antioxidant potential of roselle (Hibiscus sabdariffa L.) extracts was studied. Different plant organs, including seeds, stems, leaves, and sepals, were analyzed with respect to their water-soluble antioxidant capacity, lipid-soluble antioxidant capacity, and tocopherol content, revealing that roselle seeds are a good source of lipid-soluble antioxidants, particularly gamma-tocopherol. Roselle seed oil was extracted and characterized, and its physicochemical parameters are summarized: acidity, 2.24%; perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 20 publications
(26 reference statements)
8
91
1
5
Order By: Relevance
“…However, in Africa, they are ground into meal for human food due to their high protein content. They are also roasted to use as a substitute for coffee (Morton, 1987) and contain a substantial amount of oil that resembles that of cotton seed (Mohammed et al, 2007 andKarma andChavan, 2016).…”
Section: Issn: 2319-7706 Volume 6 Number 4 (2017) Pp 2654-2663mentioning
confidence: 99%
“…However, in Africa, they are ground into meal for human food due to their high protein content. They are also roasted to use as a substitute for coffee (Morton, 1987) and contain a substantial amount of oil that resembles that of cotton seed (Mohammed et al, 2007 andKarma andChavan, 2016).…”
Section: Issn: 2319-7706 Volume 6 Number 4 (2017) Pp 2654-2663mentioning
confidence: 99%
“…This is likely due to the anti-inflammatory activity of roselle calyxes. This research was support by many former studies that reported that roselle calyxes consist of flavonoids such as gossypetin, hibiscetine, and sabdaretin, and are also good sources of lipid-soluble antioxidants [6] and gamma tocopherols [15]. Direct evidence supports the anti-inflammatory efficacy of roselle and its capacity to reduce vasodilatation and to improve edematous conditions, thereby reducing inflammation [2][3][4]6].…”
Section: Sarwono and Suniartimentioning
confidence: 57%
“…The phytochemical, pharmacological, and toxicological properties of roselle are related to the steroids, alkaloids, saponins, flavonoids, tannins [3,11,12,15], and polyuronides contained in this plant [8]. Previous studies reported that saponin extracted from ginseng, for example, accelerates neovascularization in burn wounds on the skin of mice through a reduction in neutrophil entry to wounds, therefore lessening chronic inflammatory reactions [4,6,10].…”
Section: Sarwono and Suniartimentioning
confidence: 99%
See 1 more Smart Citation
“…The results strongly suggest that the B. elegana Choisy seed oil is a rich source of α-tocotrienol (α-T3), also similar to palm oil (Al-Saqer et al, 2004). It should be noted that tocopherols and tocotrienols have antioxidant properties and they are active as vitamin E, whose deficiency affects hemolysis in humans and nervous system development in children (Mohamed et al, 2007).…”
Section: Tocol Compositionmentioning
confidence: 99%